Are Suicidal Behaviors Contagious in Adolescence? Using Longitudinal Data to Examine Suicide Suggestion. (April 2014) - Abrutyn, Seth; Mueller, Anna S.
Durkheim argued that strong social relationships protect individuals from suicide. We posit, however, that strong social relationships also have the potential to increase individuals' vulnerability when they expose people to suicidality. Using three waves of data from the National Longitudinal Study of Adolescent Health, we evaluate whether new suicidal thoughts and attempts are in part responses to exposure to role models' suicide attempts, specifically friends and family. We find that role models' suicide attempts do in fact trigger new suicidal thoughts, and in some cases attempts, even after significant controls are introduced. Moreover, we find these effects fade with time, girls are more vulnerable to them than boys, and the relationship to the role model—for teenagers at least—matters. Friends appear to be more salient role models for both boys and girls. Our findings suggest that exposure to suicidal behaviors in significant others may teach individuals new ways to deal with emotional distress, namely by becoming suicidal. This reinforces the idea that the structure—and content—of social networks conditions their role in preventing suicidality. Social ties can be conduits of not just social support, but also antisocial behaviors, like suicidality.